HIV partner notification is effective and feasible in sub-Saharan Africa: Opportunities for HIV treatment and prevention - Brown, Lillian B (2011)
BACKGROUND: Sexual partners of persons with newly diagnosed HIV infection require HIV counseling, testing and, if necessary, evaluation for therapy. However, many African countries do not have a standardized protocol for partner notification and the effectiveness of partner notification has not been evaluated in developing countries. METHODS: Individuals with newly diagnosed HIV infection presenting to STI clinics in Lilongwe, Malawi were randomized to one of three methods of partner notification: passive referral, contract referral, or provider referral. The passive referral group was responsible for notifying their partners themselves. The contract referral group was given seven days to notify their partners, after which a health care provider contacted partners who had not reported for counseling and testing. In the provider referral group, a health care provider notified partners directly. RESULTS: 240 index patients named 302 sexual partners and provided locator information for 252. Among locatable partners, 107 returned for HIV counseling and testing; 20/82 (24%; 95% CI 15 – 34%) partners returned in the passive referral arm, 45/88 (51%; 95% CI 41 – 62%) in the contract referral arm, and 42/82 (51%; 95% CI 40 – 62%) in the provider referral arm (p<0·001). Among returning partners (n=107), 67 (64%) of were HIV-infected with 54 (81%) newly diagnosed. DISCUSSION: This study provides the first evidence of the effectiveness of partner notification in sub-Saharan Africa. Active partner notification was feasible, acceptable, and effective among STI clinic patients. Partner notification will increase early referral to care and facilitate risk reduction among high-risk uninfected partners.